The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1250/ast.37.10
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic measurement of the net transport through the Seto Inland Sea

Abstract: Abstract:The net transport through the Seto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 24 publications
3
44
1
Order By: Relevance
“…In the observation site, strong tidal currents cause vertical mixing and weaken thermal stratification (e.g., Takeoka, ; Yanagi & Okada, ). During the experimental periods, the sound speed increased with depth except occasionally for the upper few meters (Zhang et al, ). When the sound speed increases with depth, the first arrival ray is the refracted‐surface‐reflected ray with the turning depth near the seafloor.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the observation site, strong tidal currents cause vertical mixing and weaken thermal stratification (e.g., Takeoka, ; Yanagi & Okada, ). During the experimental periods, the sound speed increased with depth except occasionally for the upper few meters (Zhang et al, ). When the sound speed increases with depth, the first arrival ray is the refracted‐surface‐reflected ray with the turning depth near the seafloor.…”
Section: Methodsmentioning
confidence: 98%
“…In 2012, a CAT experiment was conducted in the eastern portion of the Aki‐Nada sea area ( nada in the SIS indicates relatively wide basins connected by relatively narrow straits) with the aim of estimating the volume transport through the SIS (Figure c). Zhang et al () analyzed the reciprocal travel time data over 6 months and concluded that the net westward transport averaged monthly for the successfully observed period was 13,100±2,500 m 3 s −1 . In the experiment, the reciprocal acoustic transmissions were conducted along one transmission line (Figure c).…”
Section: Introductionmentioning
confidence: 99%
“…Station B3 on the Bali side was sited at an abandoned platform of a natural gas pipeline 60 m offshore from the coast, and station B4 on the Java side was at the edge of a jetty in a resort hotel. The distance between B3 and B4 was 4,461 m, determined from the global positioning system (GPS) and conductivity-temperature-depth (CTD) correction [10]. The seafloor depth is about 27 m at B3 and 5 m at B4.…”
Section: Methodsmentioning
confidence: 99%
“…Here C 0 is the reference sound speed and L is the stationto-station distance [10]. For a modulation number of three cycles per digit, t r ¼ 3=10;000 ¼ 0:3 ms. For L ¼ 4;461 m and C 0 ¼ 1;500 ms À1 , V e ¼ 0:076 ms À1 and C e ¼ 0:152 ms À1 .…”
Section: Error Evaluationmentioning
confidence: 99%
See 1 more Smart Citation